REGULATORY SUPPORT PROCESSES FOREIGN INVESTMENT IN UKRAINE - Fedorov G.O. (Pressing Problems of Public Administration, 2015)
The article reviews the main aspects of the legal provision of foreign investment processes, selected forms of legal regulation of foreign investments in the market, listed the legal acts regulating investment activity in Ukraine.